Družboslovno pojmovanje primitivne religije v XIX. in v XX. stoletju - Flere, Sergej (Družboslovne razprave, 1998)
Comparison of theoretical stands on the so called "primitive religion" in the social sciences during the 19th and 20th century (after World War I) is carried out. Clear differences have been established. During the XIX century, there were numerous apodictical and mutually contradictory stands as to the nature and content of the primitive (primarily paleolithic) religion. Animism, magic, totemism, the idea of primitive mentality, ancestors` cult etc. competed as exclusive explanations. After World War I scholars, now more often also empirical investigators, became more cautious. Phenomenology of religion, functionalism and structuralism effloresce. Myth and ritual are analysed in particular. Concerning the explanation of primitive religion, shamanism is again becoming a key concept. In spite of this, difficulties as to the possibility of a clear delineation of religion remain. The neo-evolutionist explanation of R. Bellah, though not exhaustive, remains the most plausible.
Keywords: primitivna ljudstva; religija; religion; sociologija religije